Evoked otoacoustic emissions in workers exposed to noise: A review - Alcarás, Patrícia Arruda de Souza (Int Arch Otorhinolaryngol, 2012)
Introduction: The otoacoustic emissions test is an essential tool in the evaluation of auditory function, since it allows the early detection of cochlear damage of occupational origin. Objective: To present a review of the literature and analyze the effectiveness of the clinical application of the otoacoustic emissions test in workers exposed to noise. Methods: A bibliographical search covering a period of 10 years was performed in the Virtual Health Library including published articles in national and international journals indexed in the internationally recognized databases for the health sciences, LILACS, SCIELO, and MEDLINE, using the terms “otoacoustic emissions” and “occupational exposure.” The type of published article (national/international), the type and intensity of the stimulus most commonly used for the evoked otoacoustic emissions, the gender and age of the subjects, and the conclusions from the retrospective studies were all taken into consideration. Results and Conclusions: A total of 19 articles were analyzed, 7 national and 12 international, covering subjects from 17 to 77 years of age, mostly men. The type of stimulus most commonly used for the evoked otoacoustic emissions was the distortion method (12). Through this review, we have concluded that testing of evoked otoacoustic emissions in workers exposed to noise is an important tool in the early diagnosis of noise-induced cochlear hearing disorders.